ความสัมพันธ์ระหว่างองค์ประกอบของคณะกรรมการตรวจสอบกับระดับการเปิดเผยข้อมูล ของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - เพ็ญประภา ฉิมศร (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objectives of the study are twofold: (1) to study the level of aggregate, mandatory and voluntary disclosure and (2) to study the association of audit committee compositions and the level of disclosure by using unweighted disclosure index was developed to measure the level of aggregate, mandatory and voluntary disclosure, as proxied by comprehensiveness. The author collected data from financial reports and sent the questionnaires to the audit committee members of 200 listed companies in the Stock Exchange of Thailand. The methods of testing and analysis are the descriptive statistics and multiple regression analysis. The independent variables used for the study are an audit committee compositions which consisted of independence, accounting or financial expertise, numbers of audit committee member and numbers of conference of audit committee. The control variables are firm size, profitability, financial leverage and audit firms. The result indicates that the numbers of audit committee member are significantly and positively associated with the level of aggregate and mandatory disclosure. For independence, accounting or financial expertise and the numbers of conference of audit committee, they are not significantly associated with three types of disclosure. These findings may have benefits for regulators, enhancing, corporate transparency and quality of disclosure of the listed companies in the Stock Exchange of Thailand.